Uma análise da ótica do usuário de rodovias para avaliaç\~ao multicritério de projetos rodoviários - Vicente Correia Lima Neto; Daniel Rodrigues Aldigueri (Instituto de Pesquisa Econômica Aplicada (IPEA), 2015)
– The aim of this paper is to point out the need and importance of multi-criteria weighting in road project assessment in the interests of the group affected by the project. This importance is also assessed considering the actors' profile, showing the relevance of the differentiation of the weights in relation to the profile characteristics. This research was applied to one type of actor, road users, divided into two classes of drivers: driver's light vehicles (LV) and driver's heavy vehicles (HV). These impacts of the road project were analyzed in relation to the potential benefits generated for road users, by the project, corresponding to the criteria utilized in the proposed analysis methodology of road users' perception of the importance of these criteria and consequently its impact on the road project assessment. It was found that distinguishing between users according to the variables, type of vehicle used (HV or LV), region where the road will be implemented and the level of education would be of great importance in assessing road projects. It is seen that the determination of highway driver's profiles is important for obtaining adequate weights for road project assessment: this can also be done for weighting other criteria used in other existing methods of general-transport project assessment and focus on others actors.
Keywords: R42; 330; project appraisal; highways; multi-criteria analysis